(untitled) (Conference Zone, 2023)
As a rule, a child with speech disorders is very critical of his pathology, but one of the main dangers posed by speech disorders is the inhibition of intellectual development, because speech is one of the main intellectual tools. Normalization of the development of the intellect occurs as the speech difficulty is eliminated and normal word pronunciation is formed; That is why it is so important to diagnose speech pathologies in time and begin their correction.